Act Early to Prevent Infections and Save Lives: Causal Impact of Diagnostic Efficiency on the COVID-19 Pandemic - Simiao Chen; Zhangfeng Jin; Sebastian Vollmer; Till Bärnighausen; David E. Bloom (Global Labor Organization (GLO), 2021)
This paper examines the causal impact of diagnostic efficiency on the COVID-19 pandemic in China. Using an instrumental variable approach, we show that a 1-day decrease in the time taken to confirm the first case in a city publicly led to 9.4% and 12.7% reductions in COVID-19 prevalence and mortality over the subsequent six months, respectively. The impact was larger for cities that are farther from the COVID-19 epicenter, are exposed to less migration, have more responsive public health systems, and have higher-capacity utilization of health systems. Social distancing and a less burdened health system are likely underlying mechanisms.
Keywords: I18; D83; H75; I12; J61; 330; Diagnostic Efficiency; Information Disclosure; Social Distancing; COVID-19; China